By-catch in the fishery for lobsters Panulirus argus and Panulirus laevicauda, in Ceará State, Brazil - Corrêa lvo, Carlos Tassito; Santiago, Manoel Erones; Monteiro-Neto, Cassiano (Arquivos de Ciências do Mar, 2018)
This paper characterizes the speciftc composition of the úy-catch in the trap and gillnet !abster fishery, from ]une 1990 to fuly 1991 off the coast of Ceará State, Brazil, analyzing the community structure through diversity, relative abundance and species dominance índices. Fifty four species ( 44 ftshes and 10 crustaceans) belonging to 39 families were identified. The families Lutjanidae, Pomadasyidae, Chaetodontidae, Acanthuridae and Scilaridae were the most important. The stingray (Gimnura micrura), the brown tang (Acanthurus chirurgus), the white grunt (Haemulon plumieri) the parum-black (Pomacanthus paru), the hermit crabs (Petrochirus diogenes and Dardanus venosus) and the crab (Calappa ocelata) were the most representative species throughout every sampled depth. Diversity of the úy-catch was considerably high, near the maximum expected, and dominance was low. Statistical tests did not indicate significant differences of diversity between time of the year and sampling depths.